Sixth-grade students’ experiences of a digital game-based learning environment: A didactic analysis - Gök, Mustafa; İnan, Mevlüt (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2021)
Students' conceptual understanding and mathematical process skills can be improved through digital games in mathematics education. The starting point of this study is the idea of having students encounters this kind of environment. The study didactically describes the process of 6thgrade students’ experiences of a digital game-based learning environment. A combination of the Theory of Didactical Situations (TDS) and Digital Game-Based Learning (DGBL) was used in the design of the digital game. The research focused on knowledge-based interactions (teacher-studentgame) during the implementation of the game called Race with Numbers, designed in line with this synthesis. The case study, one of the qualitative research methods, was used in the study. Research participants consist of 16 middle secondary school students studying in the 6th grade in a public school. The research data were collected with a video camera and two voice recorders. The research application lasted 75 minutes. The data analysis related to the application was carried out by describing the interaction between the students and the game at stages of TDS. The study findings indicated that TDS has significant potential in designing DGBL environments. However, strong evidence is presented that such environments enable students to realize their own learning and encourage them to use mathematical process skills (such as problemsolving, reasoning, proving, and transfer). Finally, the study highlights the importance of the digital game-based learning approach in mathematics teaching for students.